2013
DOI: 10.1080/1536710x.2013.810093
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning, Psychosocial Stress, and Goal Attainment in Brain Injury Rehabilitation

Abstract: The study investigated the impact of family functioning (as measured by the Family Assessment Device) on goal attainment (as measured by a Goal Attainment Scale) and psychosocial distress (as measured by the Brief Symptom Inventory-18) among survivors of acquired brain injury in a community re-entry rehabilitation setting. The bivariate analysis suggests that participants had significantly greater goal attainment scores if they were members of families with stronger general functioning (r = .27, p < .05), stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Similarly, assessment is well-established as a fundamental process for all rehabilitation clinicians (Sander et al, 2009). The high proportion of clinicians providing client or family education (94–100%) reinforces previous findings that psycho-education is a core element of TBI rehabilitation practice (Barclay, 2013; Bishop et al, 2006). Other common areas of rehabilitation practice included provision of assessment feedback (78–100%), behaviour management and support (80–100%) and evaluation of rehabilitation outcome (71–100%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, assessment is well-established as a fundamental process for all rehabilitation clinicians (Sander et al, 2009). The high proportion of clinicians providing client or family education (94–100%) reinforces previous findings that psycho-education is a core element of TBI rehabilitation practice (Barclay, 2013; Bishop et al, 2006). Other common areas of rehabilitation practice included provision of assessment feedback (78–100%), behaviour management and support (80–100%) and evaluation of rehabilitation outcome (71–100%).…”
Section: Discussionsupporting
confidence: 81%
“…McLaughlin and Carey (1993) found that conflict between the rehabilitation team and family of TBI clients was associated with longer length of stay and lower program satisfaction. In contrast, having family members engaged in the rehabilitation process has been linked to improved client outcomes (Foster et al, 2012), particularly for clients with families with stronger functioning (Barclay, 2013).…”
Section: Barriers To Providing Rehabilitationmentioning
confidence: 99%
“…This mirrors international research documenting gender differences in community integration for men and women post-injury (Stålnacke, 2007). Also, women appeared to be more negative as regards accepting their 'new selves' than men, as previously documented (Muenchberger et al, 2010;Barclay, 2013). Recognising additional factors such as age, rural/urban divide and the extent of the disability will contribute to understanding people's experiences.…”
Section: A New Type Of Normalsupporting
confidence: 79%
“…Another theory put forward is that females may have a greater need for ongoing intervention from local support groups than their male counterparts. Significant gender differences were also reported in an American study of sixty adults with ABI investigating family functioning and ABI rehabilitation (Barclay, 2013). Again, female participants reported higher levels of psychosocial distress and higher levels of family emotional response than men.…”
Section: Understanding Gender Interactions and Differencesmentioning
confidence: 63%
“…Family members often experience significant distress and compromised quality of life in the wake of the neurobehavioral changes imposed by TBI (Rivera, Elliott, Berry, & Grant, 2008). Family members typically face high levels of stress, burden, social isolation, role changes, and other psychosocial health problems that generally do not lessen with time (Barclay, 2013;Degeneffe, 2001). The challenges and distress experienced by family members can impact the rehabilitation process as well as the recovery of the person with TBI (Sander, 2014).…”
mentioning
confidence: 99%